Testing the consistency of asymmetric interest rate pass-through: The case of Indonesia - R. Dimas Bagas Herlambang; Rudi Purwono; Rumayya (Cogent Economics & Finance, 2023)
This paper investigates the consistency of asymmetric interest rate past-trough (IRPT) using a nonlinear autoregressive distributed lag framework. Superior to the previous studies, this study exploits the historical profile of Indonesia to enrich the analysis. Asian Financial Crisis (AFC) which crashed the country in 1998 and several monetary policy changes implemented by the government offer different perspectives to grasp IRPT. The results of this study indicate that there is a consistent upward rigidity in the long-run pass-through in Indonesia. Particularly during the AFC, it is well proven that the asymmetric behavior is fickle whether disappear or bounce back to the downward rigidity. This finding demonstrates the importance of a rolling-window approach in understanding IRPT.
Keywords: C22; E43; E52; 330; asymmetries; Interest rate pass-through; rolling window estimation; structural break